Food security in the face of the 2030 : agenda cuban experience - McCormack Bequer, Maritza de la Caridad; Cruz Legón, Mayra (Universidad Pedagógica y Tecnológica de Colombia, 2022)
To reach the alimentary security is a real problem of all. It constitutes a necessary and indispensable objective for the humanity, where the governments have a fundamental paper in the development of political public that pay to this. It is required to guarantee the alimentary chains together to a nutritional education and a constant concern for the human being, like center of everything. The objective of the investigation was centered in knowing the public politicians in Cuba around reaching the alimentary security, and he/she thinks about as hypothesis the necessity of the local development that you/they allow the alimentary sovereignty and with it a nutritional security. Methods like the historical one were used logical, compared right, exegético-analytic, inductive and deductive. The results are appreciated starting from the analysis of the interpretation and application of the public politicians and the Plan of alimentary sovereignty and nutritional education. The implications of this investigation show as the results they are crisscross with the public politicians and the application of these in each territory, being indispensable a pursuit of the same ones to perfect the whole development of the application of these and to achieve the alimentary security definitively for which the country fights.